English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

So it is

(3(square root of 2)+4(square root of 5))
TIMES
(4(square root of 2)-(square root of 5))

2007-01-22 04:52:23 · 4 answers · asked by -WANTED- 3 in Science & Mathematics Mathematics

4 answers

.

This question can be solved by just simple multiplication of each term with the other...

(3√2 + 4√5)*(4√2 - √5)

= (3√2) * (4√2) + (3√2) * (-√5) + (4√5) * (4√2) + (4√5) * (-√5)

= 24 - 3√10 + 16√10 - 20

= 4 + 13√10

.

2007-01-22 05:12:49 · answer #1 · answered by Preety 2 · 0 0

let sqrt sign be: "/"

(3/2 + 4/5) ( 4/2 - /5)

24 -3/10 + 16/10 -20
4 + 13/10

2007-01-22 04:58:48 · answer #2 · answered by sh 1 · 1 0

for example square root = /

3x /2+4x/5
x
4x/2-/5

2007-01-22 06:13:17 · answer #3 · answered by birdie1990 2 · 0 0

?(9x) = 2?(x+5) (unique equation) [?(9x)]² = [2?(x+5)]² (sq. the two components to negate radical) 9x = 4(x+5) (rewrite) 9x = 4x+20 (expand) 5x = 20 (subtract 4x) x = 4 (divide by using 5) answer: x = 4

2016-12-12 17:38:40 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers